Analisa Struktur Modal dan Total Assets Turnover Terhadap Nilai Perusahaan dengan Perusahaan sektor Energi - Muhamad Rizki; Agus Munandar (Jurnal Riset Akuntansi Politala, 2026)
The purpose of this investigation is to ascertain how capital structure and total asset turnover affect the value of energy businesses listed between 2022 - 2024 on the IDX. The secondary data used in this quantitative research comes from financial data that are listed on the IDX. Corporate in the energy industry that were listed on the IDX during that time are included in the research population. Purposive sampling was used to selected a sample of 57 companies, of which 19 released consecutive financial data. Descriptive statistical analysis, multiple linear regression analysis, and traditional assumption testing are the analytic techniques employed in this work. The investigation findings demonstrate that capital structure significantly and favorably affects a company's value, although total asset turnover has no effect.